Depredation in pelagic surface longlines in the Atlantic and Indian Oceans - Muñoz-Lechuga, Rubén (2020)
Depredation has aroused great interest over the last few decades, mainly due to the expansion of distant fishing, in particular longlines. For this study, captures and depredation records were taken by scientific observers on board Portuguese commercial longline vessels in the Atlantic and Indian Oceans between 2011 and 2016. A total of 1,336 fishing sets were monitored, with a total of 86,183 fish captured, including 1,681 depredation events. The percentage of depredation tended to increase along the time series, except in the last year where a decrease was noted. Significant differences between sizes of swordfish Xiphias gladius damaged by predators were observed in the Indian Ocean but not in the Atlantic. The highest proportions of depredation were observed on tuna and small pelagic fishes in both oceans. For swordfish, the effects of spatial variables were significant on the rate of depredation events. The results provide an overview of the depredation patterns in the Portuguese pelagic longline fishery in the Atlantic and Indian Oceans, which can inform and improve fisheries management and contribute to the development of effective mitigation measures to reduce the impacts of depredation on fisheries.